Models of care for traumatically injured patients at trauma centres in British Columbia: variability and sustainability. Issue 2 (11th July 2017) - Tuyp, Benjamin; Hassani, Kasra; Constable, Lisa; Haegert, Joseph
Abstract: Background: Successful trauma systems employ a network of variably-resourced hospitals, staffed by experienced providers, to deliver optimal care for injured patients. The "model of care"—the manner by which inpatients are admitted and overseen, is an important determinant of patient outcomes. Objectives: To describe the models of inpatient trauma care at British Columbia's (BC's) ten adult trauma centres, their sustainability, and their compatibility with accreditation guidelines. Methods: Questionnaires were distributed to the trauma medical directors at BC's ten Level I-III adult trauma centres. Follow-up semi-structured interviews clarified responses. Results: Three different models of inpatient trauma care exist within BC. The "admitting trauma service" was a multidisciplinary team providing exclusive care for injured patients. The "on-call consultant" assisted with Emergency Department (ED) resuscitation before transferring patients to a non-trauma admitting service. The single "short-stay trauma unit" employed on-call consultants who also oversaw a 48-hour short-stay ward. Both level I trauma centres utilized the admitting trauma service model (2/2). All Level II sites employed an on-call consultant model (3/3), deviating from Level II trauma centre accreditation standards. Level III sites employed all three models in similar proportions. None of the on-call consultant sites believed their current care model was sustainable. Inadequate compensation, insufficient resources, and difficulty recruiting physicians were cited barriers to sustainability and accreditation compliance. Conclusions: Three distinct models of care are distributed inconsistently across BC's Level I-III trauma hospitals. Greater use of admitting trauma service and short-stay trauma unit models may improve the sustainability and accreditation compliance of our trauma system. RÉSUMÉ: Introduction: Les systèmes de soins en traumatologie qui donnent de bons résultats reposent sur un réseau d'hôpitaux dotés de diverses ressources et d'un personnel expérimenté afin de permettre une prestation optimale de soins aux blessés. Le « modèle de soins », c'est-à-dire la manière dont les personnes sont admises et surveillées, est un déterminant important de l'évolution de l'état de santé. Objectifs: L'étude visait à décrire les modèles de soins appliqués dans 10 centres de traumatologie pour adultes en Colombie-Britannique (C.-B.) et à examiner la durabilité des différents modes de prestation et le respect des lignes directrices relatives à l'agrément. Méthode: Un questionnaire a été envoyé aux directeurs médicaux de 10 centres de traumatologie pour adultes, de niveau I à III, en C.-B. Des entrevues semi-structurées de suivi ont permis de clarifier des réponses. Résultats: Il existe trois modèles de soins en traumatologie en C.-B. : le « service d'admission en traumatologie », qui consiste en une équipe pluridisciplinaire vouée à la prestation exclusive de soins aux blessés; le « consultant de garde », qui travaille en collaboration avec une équipe de réanimation du service des urgences avant le transfert des patients vers un service d'admission non spécialisé en traumatologie; et l'« unité de traumatologie de courte durée », service spécialisé en la matière, dont la prestation de soins est assurée par des consultants de garde qui supervisent également un service de soins de courte durée de 48 heures. Les centres de traumatologie de niveau I, au nombre de deux, appliquent le modèle du « service d'admission en traumatologie » (2/2). Tous les centres de niveau II appliquent le modèle du « consultant de garde » (3/3), ce qui contrevient aux normes d'agrément des centres de traumatologie de niveau II. Quant aux centres de niveau III, ils appliquent les trois modèles dans des proportions comparables. Aucun des directeurs des centres appliquant le modèle du consultant de garde ne croyait en la durabilité de ce mode de prestation. Une rétribution insuffisante, le manque de ressources et la difficulté de trouver des médecins sont tous des facteurs considérés comme des obstacles à la durabilité et au respect des normes d'agrément. Conclusions: Les trois modèles de soins ne sont pas répartis de manière uniforme dans les centres de traumatologie de niveau I à III, en C.-B. Le recours plus fréquent au modèle du service d'admission en traumatologie et à celui de l'unité de traumatologie de courte durée pourrait améliorer la durabilité du système de soins en traumatologie et la conformité aux normes d'agrément.